TADinfo: An information system for animal health - Labroth, Juan; Kamata, Akiko (Technical Centre for Agricultural and Rural Cooperation, 2005)
Juan Labroth and Akiko Kamata explain how a software package developed by the FAO is helping veterinary services to prevent outbreaks and halt the spread of animal diseases.